ChemInform Abstract: Iron‐Catalyzed Reduction of CO2 into Methylene: Formation of C—N, C—O, and C—C Bonds. Issue 4 (January 2016) - Jin, Guanghua; Werncke, C. Gunnar; Escudie, Yannick; Sabo‐Etienne, Sylviane; Bontemps, Sebastien
Abstract: Based on the use of a (dihydrido)iron complex as catalyst the conversion of hydroboranes to bis(boryl)acetal (III) using CO2 as one‐carbon source is optimized.